Design of 3D microbial anodes for microbial electrolysis cells (MEC) fuelled by domestic wastewater. Part I: Multiphysics modelling. Issue 4 (August 2021) - Lacroix, Rémy; Roubaud, Emma; Erable, Benjamin; Etcheverry, Luc; Bergel, Alain; Basséguy, Régine; Da Silva, Serge
Abstract: The performance of a microbial electrolysis cell (MEC) supplied with domestic wastewater (dWW) is essentially limited by the kinetics of the anodic bioelectrochemical reactions and the low ionic conductivity of the electrolyte. A strategy to boost-up the anodic bioelectrochemical kinetics is to use three-dimensional (3D) microbial anodes that offer a high total anodic surface area and volume density of electroactive biofilm. In this work, a 3D multiphysics model was designed to simulate the current generation and resulting hydrogen production in double and triple-compartment MECs fed continuously with dWW. Simulations indicated that optimised 3D microbial anode geometries could simultaneously increase current and chemical oxygen demand (COD) removal by 86% compared to a 2D planar graphite electrode. At a constant CEM voltage, the current produced increased with the thickness of the 3D microbial anode up to a limiting thickness of 20 mm. Beyond this value, the current was stagnant due to the predominant ohmic drop. Current generation and COD removal could be further increased by designing 3D anode geometrical arrangements that force the dWWs to flow through the porosity of the 3D microbial anode. A gain of 20% was calculated by substituting a monolithic 3D graphite anode with a 3D anode of the same thickness (20 mm) but constructed of plates stacked on top of each other and spaced 2.5 mm apart. Finally, hydrogen production performance was additionally optimised by a further + 20% by switching from a two-compartment MEC design (anode-cathode) to a three-compartment MEC design (cathode-anode-cathode). Graphical Abstract: ga1 Highlights: Multiphysics modelling is a powerful tool for designing and scaling-up MEC reactors. The active thickness of 3D microbial anodes is dependant to the electrolyte conductivity. Optimized 3D graphite electrode geometry increases hydrogen production by 86%. dWW hydrodynamics modelling can predict the COD removal performed by the MEC. A 3-compartment (cathode-anode-cathode) MEC design delivers 20% more hydrogen.